Acquired neuro-secretory defect in growth hormone secretion due to Imatinib mesylate and the efficacy of growth hormone therapy in children with chronic myeloid leukemia. (17th February 2020) - Walia, Rama; Aggarwal, Anuradha; Bhansali, Anil; Aggarwal, Anshita; Varma, Neelam; Sachdeva, Naresh; Khandelwal, Niranjan; Bansal, Deepak
Abstract: Imatinib results in growth retardation in children with chronic myeloid leukemia (CML). The study was planned to assess the GHRH-GH-IGF1 axis in children with CML, receiving Imatinib and to evaluate the efficacy of human growth hormone (hGH) therapy. Twenty children with CML, receiving Imatinib for a period exceeding 6 months, with resultant growth retardation were included. The GHRH-GH-IGF1 axis was assessed using growth hormone stimulation tests. IGF-1 generation test was performed for the evaluation of GH insensitivity. The mean age at inclusion was 15.2 years. The mean duration of treatment with Imatinib was 5.7 years. The mean decrease in height SDS since the start of Imatinib was −0.95 ( p = 0.008). IGF-1 SDS was <-2 in all the patients. 71.4% of patients had a suboptimal GH response following stimulation with GHRH-Arginine. All patients had stimulable, although a delayed GH response with glucagon stimulation. 20% of patients had GH insensitivity. Four patients were treated with hGH for a mean duration of 5.75 months, achieved normalization of IGF-1 levels and improvement in growth velocity improved from 0.21 to 0.86 cm/month. Imatinib results in an acquired neurosecretory defect in GH secretion. Treatment with growth hormone leads to an improvement in growth velocity and normalization of IGF-1.